WYBURN-MASON SYNDROME ASSOCIATED WITH MOYAMOYA DISEASE - HIRUNPAT, Siriporn; PEKANAN, Patchrin; POENPATHOM, Nakornchai (The ASEAN Journal of Radiology, 2023)
A report case of subcutaneous hemangiomas of the head and face, intraorbital hemangiomas, intracranial AVM and occlusion of distal left internal carotid artery was shown in a 17-year-old man. The association of the Wyburn-Mason Syndrome and Moyamoya disease in this patient was rare and was not seen in the literature. The imaging modalities were CT scan and angiography of the head.